2014
DOI: 10.1353/hpu.2014.0110
|View full text |Cite
|
Sign up to set email alerts
|

Response to a Patient Activation Intervention among Spanish-speaking Patients at a Community Health Center in New York City

Abstract: Patient activation describes an individual's readiness to participate in their health care. Lower levels of activation that may contribute to poor health outcomes have been documented in Latino patients. We administered a brief activating intervention directed at Spanish-speakers that sought to improve and encourage question-asking during a medical visit. We used quantitative measures of patient attitudes supplemented with open-ended questions to evaluate the effectiveness of the intervention at a community he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
0
18
1
Order By: Relevance
“…The significance of the potential measure differences between the P-PAM and PAM are most salient when considering the relation between activation and healthcare outcomes. Interventions to increase activation among immigrant Latino adults have resulted in increased comfort with asking questions of providers and increased care retention [28,29]. Similar associations between health and healthcare outcomes and P-PAM score would suggest that activation as measured by the P-PAM may still be a useful intervention target in pediatrics despite the measure limitations identified in this study, but this is not yet known.…”
Section: Discussionmentioning
confidence: 77%
“…The significance of the potential measure differences between the P-PAM and PAM are most salient when considering the relation between activation and healthcare outcomes. Interventions to increase activation among immigrant Latino adults have resulted in increased comfort with asking questions of providers and increased care retention [28,29]. Similar associations between health and healthcare outcomes and P-PAM score would suggest that activation as measured by the P-PAM may still be a useful intervention target in pediatrics despite the measure limitations identified in this study, but this is not yet known.…”
Section: Discussionmentioning
confidence: 77%
“…Out of 87 included studies, the term, sex was mentioned in 37 (42.5%) studies [ 54 58 , 60 64 , 66 , 68 , 70 , 71 , 79 , 83 , 85 , 87 , 89 , 95 , 96 , 98 , 103 , 105 , 107 , 110 , 112 , 114 , 119 122 , 126 , 128 , 130 132 ]. Gender was mentioned in 36 (41.4%) studies [ 51 , 52 , 58 , 60 , 61 , 63 , 65 , 70 , 71 , 77 , 82 , 87 , 89 , 91 , 96 99 , 101 , 104 , 106 , 112 , 114 , 117 119 , 121 , 124 , 125 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Studies have found that patient education and empowerment efforts, such as the Stanford Chronic Disease Self-Management Program and coaching with motivational interviewing, increase activation. [23][24][25][26][27][28][29][30][31] Very little research, however, has examined the clinician role in supporting patient activation. Given clinicians' key potential impact on patient behavior, this is an important area for investigation.…”
Section: Introductionmentioning
confidence: 99%